Reinterpretasi Tradisi Islam: Larangan Menikah Di Bulan Muharram (Suro) Dalam Adat Jawa - Khusaini, Muhammad; Yusman, Armanda; Ali, Zezen Zainul; Adila, Queen (Realita: Jurnal Penelitian dan Kebudayaan Islam, 2024)
The prohibition against marrying in the month of Muharram (Suro) is a deeply rooted belief among Javanese communities, including Muslims in Pakuan Baru Village, Pakuan Ratu Subdistrict, Way Kanan Regency. Although Islam does not explicitly forbid marriage in Muharram, local customs—passed down through generations—consider this month inauspicious for wedding ceremonies. This study aims to reinterpret the tradition of prohibiting marriage during Muharram in light of Islamic teachings and Javanese cultural values. Employing a descriptive qualitative approach, the research collects data through field observations, interviews with community members, religious leaders, and local elders. Findings indicate that the prohibition is still strongly upheld due to reverence for ancestral customs and the perception of Muharram as a sacred and solemn month. While this belief aligns with the Javanese ethic of spiritual caution, it also reflects a syncretic understanding that merges Islamic reverence for sacred time with local cultural interpretations. The study offers a reinterpretation that encourages critical reflection on inherited traditions while promoting harmony between religious doctrine and cultural expression